Perancangan Sistem Informasi Rekam Medis Kunjungan Rawat Jalan Menggunakan Microsoft Visual Basic 6.0 - Khairunnisyah, Khairunnisyah; Reka Dwi Saputra (Gayaku Publisher, 2023)
Puskesmas is a health service institution that performs several types of services, one of which is medical record services for outpatients. In an effort to improve the quality of health services to be more well integrated. At present the Puskesmas in the use of the system must be computerized. Currently at the Bengkulu City Decline Health Center, there are still some obstacles to the information system used, such as the outpatient section in identifying patients who will register for treatment and also in preparing reports. The purpose of this study was conducted with the aim of knowing the medical record information system for outpatient visits at the Bengkulu City Health Center. The method used in this research is to use a qualitative method with a descriptive approach by means of observation, interviews and literature study. For the system development method used, namely the Waterfall method by going through the stages of needs analysis, design, coding and testing. The results of the study were seen from the analysis of the outpatient system. Shows that the patient registration process is still recorded manually in the registration book, so that when searching for patient data it takes time because it has not been computerized. the doctor who has finished examining must record in the patient's medical record file after which it is given to the medical record officer to be recapitulated to make a report. Reporting is still manual. With this software system, it can facilitate and speed up the performance of officers in processing outpatient data, the system at the Puskesmas becomes more effective, efficient, neatly organized and well integrated.